Mobile Technology-Assisted Flipped Classroom Method to Increase the Complexity Students' Reading by Video Narrative - Siregar, Alfitriani; Sulistiani (English Lecturers and Teachers Association (ELTA), 2024)
The study aimed to find out the significance of the mobile technology-assisted flipped classroom method to increase the complexity of students' reading by video narrative through fairy story YouTube videos as a media in Junior High School. This research design is a quantitative study with an experimental research design. The population was all of the students at SMP Negeri 4 Satu Atap Panai Hulu, Indonesia. The sample used by random sampling technique was divided into two groups were experimental group taught by mobile technology-assisted YouTube video narrative and the control group taught using the reading book method. The data was collected by using pre-test and post-test and were analyzed by using the t-test formula of 16.0 SPSS. The result found that the t-test is the value of sig. (2 tailed) of 0.000<0.5 means that there was a significant effect of mobile technology-assisted flipped classroom method to increase the complexity of students' reading by video narrative through fairy story YouTube video as a media. Keywords : Flipped Classroom; mobile technology; reading; narrative video